Kinematics and Mechanical Properties of Knees following Patellar Replacing and Patellar Retaining Total Knee Arthroplasty - Rongying Huang; Yanqiang Liu; Jun Zhu (Applied Bionics and Biomechanics)
Knee injury is a common medical issue. A full understanding of the kinematics and mechanical properties of knees following total knee arthroplasty (TKA) repair utilizing patellar replacement (only the base of the patella is replaced) versus patellar retaining surgical techniques is still lacking. In the current paper, we investigated magnetic resonance (MR) imaging data from knees repaired by these two methods and evaluated total knee models created using imaging reconstruction technology that simulated gait conditions. Results revealed that patellar replacement had little influence on tibiofemoral kinematics, although the tibia-surface equivalent stress increased slightly. By contrast, patellar replacement had a significant influence on the patellofemoral joint; patellar internal rotation, external rotation, and medial-lateral translation were all increased. Moreover, the stress distribution on patellar prostheses was altered, resulting in an increased surface maximal equivalent stress on the corresponding area. Moreover, during the gait cycle, we found that the area with maximal equivalent stress shifted its position. Finally, the patellofemoral joint showed decreased motion stability. From the view of kinematics and mechanics, this paper suggests that patella should be retained during TKA if it is possible. The present study presented approaches and technologies for evaluating kinematics and mechanical properties of total knee joint after TKA under gait loads.